Simple and cost-effective fluorescent labeling of 5-hydroxymethylcytosine. (7th October 2016) - Shahal, Tamar; Green, Ori; Hananel, Uri; Michaeli, Yael; Shabat, Doron; Ebenstein, Yuval
Abstract: The nucleobase 5-hydroxymethylcytosine (5-hmC), a modified form of cytosine, is an important epigenetic mark related to regulation of gene expression. 5-hmC levels are highly dynamic during early development and are modulated during the progression of neurodegenerative disease and cancer. We describe a spectroscopic method for the global quantification of 5-hmC in genomic DNA. This method relies on the enzymatic glucosylation of 5-hmC, followed by a glucose oxidation step that results in the formation of aldehyde moieties that are covalently linked to a fluorescent reporter by oxime ligation. The fluorescence intensity of the labeled sample is directly proportional to its 5-hmC content. We show that this simple and cost-effective technique is suitable for quantification of 5-hmC content in different mouse tissues.